Neurocircuitry of limbic dysfunction in anorexia nervosa. (January 2015) - Lipsman, Nir; Woodside, D. Blake; Lozano, Andres M.
Abstract: Anorexia Nervosa (AN) is a serious psychiatric condition marked by firmly entrenched and maladaptive behaviors and beliefs about body, weight and food, as well as high rates of psychiatric comorbidity. The neural roots of AN are now beginning to emerge, and appear to be related to dysfunctional, primarily limbic, circuits driving pathological thoughts and behaviors. As a result, the significant physical symptoms of AN are increasingly being understood at least partially as a result of abnormal or dysregulated emotional processing. This paper reviews the nature of limbic dysfunction in AN, and how structural and functional imaging has implicated distinct emotional and perceptual neural circuits driving AN symptoms. We propose that top-down and bottom-up influences converge on key limbic modulatory structures, such as the subcallosal cingulate and insula, whose normal functioning is critical to affective regulation and emotional homeostasis. Dysfunctional activity in these structures, as is seen in AN, may lead to emotional processing deficits and psychiatric symptoms, which then drive maladaptive behaviors. Modulating limbic dysregulation may therefore be a potential treatment strategy in some AN patients.